Morphological classification of male face images of three major ethnic groups for retrieval during identification - Ghouse, Hazzreen Effendy Md (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Human faces have their individual uniqueness. The morphology of the face is influenced by the genetic and epigenetic factors. The factors that contribute to individuality are exerted on every faces. The present human population originated from three distinct stock races, Mongoloid, Caucasoid and Negroid. The subsequent breakdown of the geographic barriers and mixing up of the gene pools due to factors such as marriage between stock races has been the cause for the diversity among features of the present population in general, and specifically in the facial structure. Epigenetic influences such as extreme climate, and differences in atmospheric pressure, has caused physical alteration in the human physical traits. Three major ethnic groups, Malay, Chinese and Indian that have originated in different geographical regions but are now living in Malaysia as Malaysian national are studied in this research for identifying facial features that manifest significant relationship to ethnic affiliation. The data collected from photogrammetric measurement of the scaled face images that were recorded in a controlled manner from each of the 105 volunteering individuals were analysed using one-way ANOVA. These ethnic groups were found to exhibits significant differences in twenty out of the total twenty-four anthropometric measurements taken.